The Effect of Financial Literacy, Lifestyle and Self-Control on Online Shopping Consumptive Behavior - Wijaya, Nica Putra; Yuniningsih, Yuniningsih (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
This research aims to examine the influence of financial literacy, lifestyle, and self-control on consumer online shopping behavior among students at the Faculty of Economics and Business, East Java Veteran Development University. The research method used is quantitative. The population in this study consisted of 4231 active students from the Faculty of Economics and Business, Veteran Development University, East Java, using a stratified random sampling technique with the Slovin formula, which produced a sample of 100 respondents. Data collection was carried out through distributing questionnaires, while the data analysis technique used SEM PLS with Smart PLS software. The results of this research show that financial literacy and self-control have a negative and significant effect on the consumptive behavior of students at the economics and business faculty at East Java Veteran Development University. This shows that financial literacy and good self-control will create moderate consumptive behavior. The results of this research also prove that lifestyle has a positive and significant effect on the consumer behavior of students at the Faculty of Economics and Business, East Java Veteran Development University. This shows that a high lifestyle will also create high consumer behavior.